Georgia : 2009 Article IV Consultation and Second Review Under the Stand-By Arrangement; Staff Report; Press Release and Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report, 2009)
This 2009 Article IV Consultation highlights that the fiscal deficit in Georgia widened markedly in 2008. The composition of spending improved from high defense and election outlays in the first half of the year to infrastructure and social spending in the second half. Executive Directors have observed that the Georgian economy has been seriously affected by the August 2008 armed conflict, and now by the global downturn. Directors have supported the authorities' plans to contain the economic slowdown through a donor-financed fiscal stimulus and a reorientation of expenditures.